Dissection on the Current Sustainability Concepts - Dwivedi, Komal (European Journal of Sustainable Development, 2018)
The paper deals with a cluster of perspectives upon the revolving concepts of the sustainability in economic, cultural and most importantly the environmental sphere. These concepts correlate economy with the environment and its general components that we are composed of or which facilitate our day to day living. The absurdity of the human actions has shifted the question mark from development to survival. The mankind needs a general yet specific and effective mechanism to maintain the round ball as a life supporting planet. The research has its major concern over the corelation of the spheres for the effective working of the model of sustainable development. The spheres are interdependent on each other for their existence. The analysis has been done on the basis of the Brundtland report. The research deals Formulation of different guidelines for different member nations with consideration of the European Union perspective. The research brings out the essence of the three essentials of sustainable development optimum utilization of resources, no wastage of resources and preservation of resources. There also have been perspectives on possible growth and development described in the research.